2014
DOI: 10.1007/s13197-014-1385-8
|View full text |Cite
|
Sign up to set email alerts
|

Oryzanol as natural antioxidant for improving sunflower oil stability

Abstract: Sunflower oil is being made shelf stable by the incorporation of synthetic antioxidants such as tertiary butyl hydroquinone (TBHQ), while natural antioxidants like oryzanol and tocopherols can also be used. The aim of the current investigation was to evaluate the antioxidant effect of natural oryzanol (Oz) concentrate (15.5 % oryzanol) and purified Oz (80 % oryzanol) on oxidative and thermal stability of sunflower oil. Sunflower oil was incorporated with Oz concentrate to provide 0, 0.12, 0.25, 0.50, 0.84, 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Zambiazi et al ( 2007 ) studying sunflower oils found smaller amounts of oleic acid (15.26 and 16.86%) and higher contents of linoleic acid (71.17 and 70.69%) compared to the results demonstrated in our research. Sunil et al ( 2015 ) also demonstrated the lower level of oleic acid and higher amount of linoleic acid in SFO (23.0 and 66.2% for oleic and linoleic acids, respectively) as compared to the present work. Differences in fatty acid composition of SFO and SBO are mostly determined by plant genotype and environmental conditions, particularly temperature, water supply, and more generally agro-climatic conditions (Castro and Leite 2018 ; Reena Rani and Sharma 2017 ; Clemente and Cahoon 2009 ).…”
Section: Resultssupporting
confidence: 64%
“…Zambiazi et al ( 2007 ) studying sunflower oils found smaller amounts of oleic acid (15.26 and 16.86%) and higher contents of linoleic acid (71.17 and 70.69%) compared to the results demonstrated in our research. Sunil et al ( 2015 ) also demonstrated the lower level of oleic acid and higher amount of linoleic acid in SFO (23.0 and 66.2% for oleic and linoleic acids, respectively) as compared to the present work. Differences in fatty acid composition of SFO and SBO are mostly determined by plant genotype and environmental conditions, particularly temperature, water supply, and more generally agro-climatic conditions (Castro and Leite 2018 ; Reena Rani and Sharma 2017 ; Clemente and Cahoon 2009 ).…”
Section: Resultssupporting
confidence: 64%
“…The mixture of 0.1% ME + 0.02% α‐T exhibited a higher synergistic effect (35.8%) than the mixture of 0.1% ME + 0.02% AA (2.2%), while 0.1% ME + 0.02% CA showed a little antagonism (−3.3%). α‐T, as a kind of antioxidant, has remarkable free radical scavenging activity and strong antioxidant power (Sunil, Srinivas, Kumar, & Krishna, ). It has been reported that the combination of α‐T and green tea extract showed synergistic effect in sunflower oil (Yin, Becker, Andersen, & Skibsted, ).…”
Section: Resultsmentioning
confidence: 99%
“…thermal oxidation. To evaluate the contribution of antioxidant agents, the content of antioxidants agents in RBO and other edible oils (SO and RPO) was examined by comparing the loss of the antioxidant contents during the thermal oxidation 2,[21][22][23][24] .…”
mentioning
confidence: 99%